2006
DOI: 10.1242/jcs.03285
|View full text |Cite
|
Sign up to set email alerts
|

Integrity of all four transmembrane domains of the tetraspanin uroplakin Ib is required for its exit from the ER

Abstract: SummaryIntegrity of all four transmembrane domains of the tetraspanin uroplakin Ib is required for its exit from the ER

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…Although the precise role of these polar residues in tetraspanin function remains unknown, recent studies suggest that the strong polar residues in CD9, CD81, and UPIb are involved in molecular packing, ie, the interactions between TM segments. [13][14][15] This notion agrees with earlier observations made from other TM proteins that TM polar residues can mediate peptide-peptide interactions within the lipid bilayer. 16 -20 Furthermore, studies from T cell receptor demonstrated that the TM polar residues contribute to the assembly, cell surface expression, and signaling of T cell receptor, [21][22][23] underscoring the biological significance of TM polar residues.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…Although the precise role of these polar residues in tetraspanin function remains unknown, recent studies suggest that the strong polar residues in CD9, CD81, and UPIb are involved in molecular packing, ie, the interactions between TM segments. [13][14][15] This notion agrees with earlier observations made from other TM proteins that TM polar residues can mediate peptide-peptide interactions within the lipid bilayer. 16 -20 Furthermore, studies from T cell receptor demonstrated that the TM polar residues contribute to the assembly, cell surface expression, and signaling of T cell receptor, [21][22][23] underscoring the biological significance of TM polar residues.…”
supporting
confidence: 87%
“…2 also found in tetraspanin UPIb, in which a mutation of the Glu residue in the third TM domain causes the ER retention of UPIb. 15 We found in this study that the Asn 17 residue in the first TM region of CD82 unlikely plays a role of CD82's first TM region in the ER exit. In addition, the Asn 17 residue appears not to be needed for the dimerization of CD82, although the corresponding polar residue in the CD9 TM1 helix is involved in the homodimerization of CD9.…”
Section: Why Are the Tm Polar Residues Important For The Function Of mentioning
confidence: 61%
See 2 more Smart Citations
“…The tetraspanin CD81 facilitates the processing and transport of the glycoprotein CD19, starting with its requirement for exit from the endoplasmic reticulum to the processing and glycosylation of CD19 (Shoham et al, 2006). The tetraspanins uroplakin Ia and uroplakin Ib allow transit of the nontetraspanin uroplakins UPII and UPIII from the Golgi to the cell surface to form urothelial plaques (Tu et al, 2006). We now provide evidence for a role of CD9 in processing and cell-surface presentation of TGFα, suggesting similar effects on all TGFα-family proteins.…”
Section: Cd9 Enhances Tgfα Presentation At the Cell Surface And Redismentioning
confidence: 99%